The Effect of Medical Students’ Problem-Solving Perceptions and Achievement on Clinical Reasoning Levels - Murat Tekin; Mustafa Onur Yurdal; Ibrahim Uysal; Aysen Melek Aytug Kosan; Cetin Toraman (Journal of Education in Science, Environment and Health)
Clinical reasoning is important in medical education in terms of achieving the purpose of clinical practice. 3 cases in which clinical reasoning prepared by relevant experts from 3 different departments were applied to Year-5 students. As an indicator of academic success, the final grade of the internship and the general success average were taken. Problem solving perception scale was applied. This research aimed to examine the relationships between the problem solving, clinical reasoning and academic achievement levels of medical students. It was observed that clinical case evaluations showed a positive correlation with each other, a positive correlation was found between clinical case evaluations and problem solving perception, and the final grade of internship and GPA did not correlate with both clinical case assessment and problem solving perception. It is necessary to determine whether the clinical reasoning processes are used adequately by the students in medical education and the education programs should be reviewed and arranged accordingly.